Information flow in times of crisis: The case of the European banking and sovereign sectors - Mardi H. Dungey; Stan Hurn; Shuping Shi; V. V. Volkov (Econometrics, 2019)
Crises in the banking and sovereign debt sectors give rise to heightened financial fragility. Of particular concern is the development of self-fulfilling feedback loops where crisis conditions in one sector are transmitted to the other sector and back again. We use time-varying tests of Granger causality to demonstrate how empirical evidence of connectivity between the banking and sovereign sectors can be detected, and provide an application to the Greek, Irish, Italian, Portuguese and Spanish (GIIPS) countries and Germany over the period 2007 to 2016. While the results provide evidence of domestic feedback loops, the most important finding is that financial fragility is an international problem and cannot be dealt with purely on a country-by-country basis.
Keywords: C22; G01; 330; financial crises; diabolical loop; banking; sovereign debt